Corporate Debt and Stock Returns: Evidence from U.S. Firms During the 2020 Oil Crash - Rabah Arezki; Caleb Cho; Ha Nguyen; Kate Nguyen; Anh Pham (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper explores the effect of oil price fluctuations on the stock returns of U.S. oil firms using a strategy of identification through heteroskedasticity exploiting the 2020 oil crash. Results are twofold. First, we find that a decline in oil prices statistically significantly reduces stock returns of oil firms. On average, a one percent decline in oil prices leads to a 0.44 percent decline in stock prices. Second, results point to the "irrelevance" of debt in mediating the effect of oil prices on stock returns of oil firms. The liquidity backstop provided by the Federal Reserve appears not to have muted the role of debt for oil firms.
Keywords: E44; G12; Q43; 330; oil prices; stock returns; debt